Instruction Of Science in Rural Junior High School - Wiworo Retnadi Rias Hayu; Anna Permanasari; Omay Sumarna; Sumar Hendayana (Universitas Djuanda, 2021)
The teacher is an essential component of learning. Learning that is often focused by the government is learning in urban schools. Even though rural schools also have the same right to consider. Longer distances and access to schools that are more difficult to reach causes a lack of attention in rural areas schools. Learning in rural areas also requires attention to improve the quality of teaching. Knowing learning activities in rural schools is very important because it will understand what learning needs to be improved. The purpose of the research is to find out how teaching science in rural schools. This research uses mixed methods with the Taxonomy Development Model research design. The phase of QUAL is carried out to identify important variables. The development of a taxonomy or classification system, the development of theories that are not yet stable, and supporting it is a test in the phase of QUAN to obtain more thorough study results. The findings of this study illustrate that learning begins with answering questions, so students are enthusiastic. The next learning activity showing films about the reproduction of students was very excited about learning. The obstacle found in learning is the lack of preparation in the learning that is done so that time is wasted to condition the video playback.